MODEL PENGENDALIAN KADAR GULA DARAH PENDERITA DIABETES MELLITUS - Juwita, Lisavina; Febrina, Wiwit (Jurnal Endurance, 2018)
According to the International Diabetes Federation (IDF) there are 382 million people living with diabetes in the world by 2013. It is estimated that of the 382 million people, 175 million of whom remain undiagnosed, so the danger of developing progressive complications unwittingly and without prevention. Complications from diabetes can be prevented or delayed by keeping blood sugar levels are in the normal category so that metabolism can be well controlled. Blood sugar levels can be maintained by a healthy lifestyle. The purpose of this study was to determine the control of blood sugar levels by making healthy lifestyle in patients with diabetes mellitus type II in London in 2017: a grounded theory study. Participants in the study of 18 people. Intake of participants in this study begins with purposive sampling. The results showed the main concept of grounded theory is "Behavior Control Blood Sugar Levels". Forms of behavior in blood sugar control in this study consisted of a) the bodys response to changes result DM, b) forms of motivation patients with DM, c) Physical Activity DM patients, d) Compliance diet, e) Management DM therapy, f) Compliance controls, g) A healthy lifestyle DM family, h) Impact of changes in lifestyle. The results of this study can serve as a reference, especially for people with diabetes mellitus and family in order to implement the behavior of controlling blood sugar levels.Â Â Menurut International Diabetes Federation (IDF) terdapat 382 juta orang yang hidup dengan diabetes di dunia pada tahun 2013. Diperkirakan dari 382 juta orang tersebut, 175 juta diantaranya belum terdiagnosis, sehingga terancam berkembang progresif menjadi komplikasi tanpa disadari dan tanpa pencegahan. Komplikasi akibat diabetes dapat dicegah atau ditunda dengan menjaga kadar gula darah berada dalam kategori normal sehingga metabolisme dapat dikendalikan dengan baik.Â  Kadar gula darah dapat dijaga dengan melakukan gaya hidup yang sehat. Tujuan penelitian ini adalah untuk mengetahui pengendalian kadar gula darah dengan melakukan gaya hidup sehat pada penderita diabetes mellitus tipe II di Bukittinggi tahun 2017: study grounded theory. Partisipan dalam penelitian sebanyak 18 orang. Pengambilan partisipan dalam penelitian ini diawali dengan purposive sampling. Hasil penelitian didapatkan Konsep utama dari grounded theory adalah âPerilaku Pengendalian Kadar Gula Darahâ. Bentuk perilaku pengendalian gula darah dalam penelitian ini terdiri dari a) Respon tubuh terhadap Perubahan Akibat DM, b) Bentuk motivasi pasien DM, c) Aktivitas Fisik Pasien DM, d) Kepatuhan diet, e) Manajemen terapi DM, f) Kepatuhan melakukan kontrol, g) Gaya hidup sehat keluarga DM, h) Dampak perubahan gaya hidup. Hasil penelitian ini dapat menjadi referensi khususnya bagi penderita diabetes mellitus dan keluarga agar menerapkan perilaku pengendalian kadar gula darah.Â